Rift to post-rift evolution of a passive continental margin: the Ponta Grossa Arch, SE Brazil - Franco-Magalhaes, A. O. B. [UNESP]; Hackspacher, Peter Christian [UNESP]; Glasmacher, U. A.; Saad, A. R. [UNESP] (Springer, 2010)
Low-temperature thermochronology was applied at the Brazilian passive continental margin in order to understand and reconstruct the post-rift evolution since the break-up of southwestern Gondwana. Thermochronological data obtained from apatite fission-track analysis of Neoproterozoic metamorphic and Paleozoic to Mesozoic siliciclastic rocks as well as Mesozoic dikes and alkaline intrusions from the Ponta Grossa Arch provided ages between 66.2 (1.3) and 5.9 (0.8) Ma. These data clearly indicate a post-rift reactivation during Late Cretaceous and Paleogene times. Integrating the results of older thermochronological studies, the reactivation of the southeastern Brazilian margin could be described in three main phases related to the rift to post-rift evolution of SE Brazil. Furthermore, the spatial distribution of age data indicates the presence of two age groups: a NE age-group (NE of Curitiba), with ages around 20 Ma and a SW age-group (Curitiba and NW) with ages of around 50 Ma. The change of ages follows the NW-SE trending So Jernimo-CuriA(0)va fault zone that can be traced offshore into the southern end of the Santos basin. Within the Santos basin, this lineament ends up to the salt occurrence in the south and seams to play a major role in the structural evolution of the Santos basin and the Rio Grande Rise. Sedimentological studies in the Santos basin evidenced that the transport direction changed in Miocene from WNW to WNW/NNW. During the Oligocene and earlier, the sediments were transported mainly from southeastwards to the direction of the Curitiba area into the Santos basin. Within the Miocene, an additional transport direction from an area north of Curitiba developed.
Keywords: Apatite low-temperature thermochronology; Southeastern Brazil; Late Cretaceous-Paleogene reactivation; Santos basin; Post-rift exhumation; Rio Grande Rise